2021
DOI: 10.3389/fendo.2021.603158
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Efficacy of Immediate Versus Delayed Frozen–Thawed Embryo Transfer on the Ongoing Pregnancy Rate After a Failed IVF Attempt: Study Protocol for a Randomized, Non-Inferiority, Parallel-Group, Controlled Trial

Abstract: IntroductionIn clinical practice, the ideal time at which to perform a Frozen–thawed Embryo Transfer (FET) after a failed In-vitro Fertilization-embryo Transfer (IVF-ET) is still unclear to most practicing physicians. In addition, physicians often delay the introduction of FET due to concerns on the possible residual effects of ovarian hyperstimulation, which may interfere with the regular menstrual cycle. Moreover, given that most of the published studies on the topic are retrospective with contradictory find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Some studies believe that the cause for the failure of embryo implantation is mainly due to the adverse effect of supraphysiological doses of hormones that stimulate ovulation on endometrial receptivity, resulting in the early opening of the “implantation window”. On the other hand, 10%–20% of patients have low levels of hormones, which can cause the endometrium to develop out of sync with the embryo [ 9 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies believe that the cause for the failure of embryo implantation is mainly due to the adverse effect of supraphysiological doses of hormones that stimulate ovulation on endometrial receptivity, resulting in the early opening of the “implantation window”. On the other hand, 10%–20% of patients have low levels of hormones, which can cause the endometrium to develop out of sync with the embryo [ 9 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is concluded that delaying two or more menstrual cycles may not have any advantage over continuous cycles. The results of a newly published randomized controlled trial showed that for women who received the rst FET after the failure of the fresh embryo transfer (ET) cycle, although the fresh et failed, the immediate FET had no adverse effect on the nal pregnancy outcome compared with the delayed FET [29] . Clinically, the reason why patients or doctors choose to receive delayed treatment may be that they are worried that the ovulation induction scheme will have an adverse impact on the ovary, endometrium, or endocrine environment, which were not bene cial for fertilization and implantation.…”
Section: Discussionmentioning
confidence: 99%
“…All couples provided voluntary written informed consents before participation. The study protocol was as previously published [ 23 ]. This trial was registered with chictr.org.cn (Identifier: ChiCTR2000033313).…”
Section: Methodsmentioning
confidence: 99%